Uteroplacental insufficiency reduces rat plasma leptin concentrations and alters placental leptin transporters: ameliorated with enhanced milk intake and nutrition - Briffa, Jessica F. (J Physiol, 2017)
KEY POINTS: Uteroplacental insufficiency compromises maternal mammary development, milk production and pup organ development; this is ameliorated by cross‐fostering, which improves pup growth and organ development and prevents adult diseases in growth‐restricted (Restricted) offspring by enhancing postnatal nutrition. Leptin is transported to the fetus from the mother by the placenta; we report reduced plasma leptin concentrations in Restricted fetuses associated with sex‐specific alterations in placental leptin transporter expression. Pup plasma leptin concentrations were also reduced during suckling, which may suggest reduced milk leptin transport or leptin reabsorption. Mothers suckled by Restricted pups had impaired mammary development and changes in milk fatty acid composition with no alterations in milk leptin; cross‐fostering restored pup plasma leptin concentrations, which may be correlated to improved milk composition and intake. Increased plasma leptin and altered milk fatty acid composition in Restricted pups suckling mothers with normal lactation may improve postnatal growth and prevent adult diseases. ABSTRACT: Uteroplacental insufficiency reduces birth weight and adversely affects fetal organ development, increasing adult disease risk. Cross‐fostering improves postnatal nutrition and restores these deficits. Mothers with growth‐restricted pups have compromised milk production and composition; however, the impact cross‐fostering has on milk production and composition is unknown. Plasma leptin concentrations peak during the completion of organogenesis, which occurs postnatally in rats. Leptin is transferred to the fetus via the placenta and to the pup via the lactating mammary gland. This study investigated the effect of uteroplacental insufficiency on pup plasma leptin concentrations and placental leptin transporters. We additionally examined whether cross‐fostering improves mammary development, milk composition and pup plasma leptin concentrations. Fetal growth restriction was induced by bilateral uterine vessel ligation surgery on gestation day 18 in Wistar Kyoto rats (termed uteroplacental insufficiency surgery mothers). Growth‐restricted (Restricted) fetuses had reduced plasma leptin concentrations, persisting throughout lactation, and sex‐specific alterations in placental leptin transporters. Mothers suckled by Restricted pups had impaired mammary development, altered milk fatty acid composition and increased plasma leptin concentrations, despite no changes in milk leptin. Milk intake was reduced in Restricted pups suckling uteroplacental insufficiency surgery mothers compared to Restricted pups suckling sham‐operated mothers. Cross‐fostering Restricted pups onto a sham‐operated mother improved postnatal growth and restored plasma leptin concentrations compared to Restricted pups suckling uteroplacental insufficiency surgery mothers. Uteroplacental insufficiency alters leptin homeostasis. This is ameliorated with cross‐fostering and enhanced milk fatty acid composition and consumption, which may protect the pups from developing adverse health conditions in adulthood.